2010
DOI: 10.1002/jso.21519
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive surgery plus hyperthermic intraperitoneal chemotherapy to treat gastric cancer with ascites and/or peritoneal carcinomatosis: Results from a Chinese center

Abstract: CRS plus HIPEC could offer survival advantage for selected GC patients with PC and/or ascites, with acceptable safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Recent studies on GC patients with PM treated with cytoreductive surgery (CRS) and HIPEC reported 1-year OS rates ranging from 35.5 to 50% (Table III) (25)(26)(27)(28)(29)(30)(31)(32). Our results are similar, but considered encouraging, due to the avoidance of surgical trauma.…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies on GC patients with PM treated with cytoreductive surgery (CRS) and HIPEC reported 1-year OS rates ranging from 35.5 to 50% (Table III) (25)(26)(27)(28)(29)(30)(31)(32). Our results are similar, but considered encouraging, due to the avoidance of surgical trauma.…”
Section: Discussionsupporting
confidence: 79%
“…The abstracts of these 145 articles were reviewed carefully and a further 42 articles had full text review. Ultimately, 17 articles were included in this review and summarized in Table 1 [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Of the 17 articles included in the review, 1 was a systematic review, 1 was a randomized controlled trial, 11 were prospective studies (7 case series, 4 case controls and 1 prospective randomized trial) and the remaining 4 were retrospective studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…The completeness of cytoreduction was found to be a prognostic factor in 11 studies [26][27][28][29][30][31][32][33][35][36][37]. Glehen et al showed in 2004 that with a CC score of 0 or 1, the median overall survival improved from 10.3 months to 21.3 months [27].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…Even in patients where a CCR-0 cannot be undertaken, a nearly complete resection or CCR-1 can still achieve a longer survival time compared with that of patients with large residual tumor nodules left (10). This implies that a more radical surgery strategy may be taken into consideration.…”
Section: A B C Dmentioning
confidence: 99%
“…The efficacy of IPC in PC of gastric origin has not yet been fully understood, due to the rapid development of the disease and the short patient survival times. However, IPC has been considered as a potential therapy for PC (1,9), with studies demonstrating a median survival time of 6.1-11.5 months after IPC treatment in patients with PC originating from gastric cancer (3,(10)(11)(12). Despite this, the median overall survival (OS) time of patients receiving IPC treatment varies, indicating that there may be confounding factors also affecting survival.…”
Section: Introductionmentioning
confidence: 99%